Hepatitis B infection and risk factors among pregnant women and their male partners in the Baby Shower Program in Nigeria: a cross-sectional study - Talla, Carol (Trop Med Int Health, 2020)
OBJECTIVES: To determine the population prevalence and determinants of Hepatitis B (Hep B) status, and status discordance, among pregnant women and their male partners in Nigeria. METHODS: Cross-sectional study assessing the seroprevalence of Hep B virus in a cohort of 16, 920 pregnant women and their male partners in northcentral Nigeria. Rapid HBsAg antibody test was used for Hep B diagnosis. Demographic, socioeconomic and behavioural information was collected through interviewer-administered questionnaires, and evaluated as determinants of Hep B status and couple status discordance using logistic regression. RESULTS: Of 16,920 participants who had a Hep B test result, 6,750 couples and 1,316 discordant couples were identified. The prevalence of Hep B among all participants was 10.9%, with lower prevalence among pregnant women (10.2%) than their male partners (11.9%), p<0.001. The prevalence of Hep B sero-discordance among couples was 19.5% (1,316/6,750). Younger age, prior Hep B testing, and a prior positive Hep B test increased the odds of Hep B infection while being a woman decreased the odds of Hep B among all participants, and among couples. Furthermore, polygamy (adjusted odds ratio [AOR]:1.49, 95% confidence interval [CI]:1.19–1.87), prior Hep B testing (AOR:2.38, 95% CI:1.14–4.97) and a prior positive Hep B test result were significant determinants of status discordance among the participating couples. CONCLUSION: The prevalence of Hep B among pregnant women and their male partners in northcentral Nigeria is high. A large-scale intervention is required to reduce Hep B prevalence in this setting.